FESTIVAL ANAK MUSLIM: PENGUATAN SPIRIT KEISLAMAN GENERASI ALPHA MELALUI PENANAMAN NILAI FIQIH DI TPA BAITULLAH DESA SIDOMULYO - Rahma Putri Widyaningsi; Muhammad Ridho Khawarizmi; Ulfa Jamilatul Farida; Faelasup Faelasup; Muchammad Abdul Basir; Resti Novia Rahayu; Nur Afni Pratiwi; Mega Kurnia Wati; Rosaliana Rosaliana; Baiq Uswatun Hasanah; Rafinah Rafinah; Abdul Rahman A; Sarlina Sarlina; Alda Maulidya; Nurul Wardhani Safira Putri; Muhammad Ilham (El-Madaniyah : Jurnal Pengabdian Masyarakat, 2026)
This Community Service Program (Pengabdian Kepada Masyarakat/PKM) aims to instill fiqh values from an early age in Generation Alpha children through the Muslim Children’s Festival at TPA Baitullah, Sidomulyo Village. Generation Alpha is a generation that grows up amid rapid digital technological development, thus requiring creative, enjoyable, and developmentally appropriate educational approaches. The main issue addressed is th e limited understanding among TPA children of basic fiqh practices in daily life, such as purification rituals, prayer, etiquette in worship, and Islamic behavior. The PKM implementation employs a participatory and educational approach through various festival activities, including the delivery of fiqh materials, interactive quizzes, Islamic educational games, adhan competitions, and memorization contests of prayers and short surahs. These activities involve TPA students, ustadz and ustadzah, university students, and the surrounding community as a form of collaborative effort to strengthen Islamic education. The results indicate an increase in children’s understanding and enthusiasm for learning fiqh, as well as a heightened awareness of applying fiqh values in everyday life. The Muslim Children’s Festival has proven to be an effective medium for realizing the Islamic spirit of Generation Alpha through contextual and enjoyable fiqh value education.